Faire littérature autrement - Dylan Bovet (Itinéraires, 2023)
Latin epigraphic poems—the carmina epigraphica—hold a special place in Latin literary studies. This poetry inscribed on the stones of epitaphs, of dedications or on Pompeian walls are de facto outside the book, on display. This article examines the processes of publishing and circulation of the carmina in their original context and then through their reception since Late Antiquity, which moved them from stone to book. In doing so, it draws on the pragmatics of the Latin carmen, the anthropology of writing and reading, and modern literary criticism to rethink, across time, the modalities of publication, the role of the author function and also that of the reader. The fact that the Latin epigraphic poems were transmitted through books has profoundly transformed their meaning and reception within the epigraphic canon, on the fringe of the classical canon. The correct historicisation of these elements and the notions they cover is decisive in defining what constitutes literature.